Does Financing Structure Relates to Liquidity Risk? A Comparative Study of Islamic and Conventional Banks of Pakistan - Hassnian Ali; Hussain Mohi-ud-Din Qadri; Atta Ul Mustafa (Universitas Muhammadiyah Yogyakarta, 2021)
The purpose of this paper is to find out whether financing in specific sectors increase bank liquidity risk and how this goes on with both Islamic and conventional banks. The paper used pooled regression, fixed effect model and random effect model decided on the basis of dummy joint significant test. The result shows that only financing concentration (SPEC) proved to have significant association with Islamic and overall banking sector for short run. And all other banks specific variables are unable to show a significant result. While the macroeconomic variable GDP and Inflation have a strong relationship in both long run and short run time period. This paper add value to the existing literature on liquidity risk under the new indicators issued by Basel III.